Life and work of Milorad Botić: An essay in honor of Milorad Botić (1913-2007) - Tomin, Jelena (Glasnik Advokatske komore Vojvodine, 2025)
Milorad Botić was one of the most prominent figures at the Bar Association of Vojvodina. He left an indelible mark in the Glasnik of the Bar Association of Vojvodina, Journal for legal theory and practice, as the editor-in-chief and also as the author of numerous works in the Glasnik. He was a prolific writer with several published books, collections of poems and articles.
Keywords: legal profession, Glasnik of the Bar Association of Vojvodina, Milorad Botić.